Pengaruh Model Pembelajaran Kooperatif Tipe Diskursus Multy Reprecentacy (DMR) terhadap Hasil Belajar Matematika - Febrianti, Nadila; Rusdi, Rusdi; Rahmi, Ulva; Rahma, Tasnim (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2026)
The poor performance of eighth grade mathematics students of SMP Negeri 4 Bukittinggi became the driving force of this study.  Continued reliance on traditional teacher-centered forms of education is a major contributor.  The purpose of this study was to determine whether the paradigm of cooperative learning Multy Reprecentacy (DMR) can help students learn mathematics better.  Using a static group comparison design, the study was a preparation for the experiment.  Students from two randomly selected classes-Class VIII D as the experimental group and Class VIII F as the control group-formed the study sample.  An educational assessment tool in the form of a test designed to measure learning outcomes.  Minitab and T-test were used to analyze the data.  According to the findings, the value of thitung= 2.34 is more than ttabel=1.67 and the value of k= 0.012 is less than 0.05.  DMR-type cooperative learning models have a major impact on student math achievement.  Compared to more traditional learning models, DMR models provide better results.